Dietary niches of endemic and range-expanding salmonids in the western Canadian Arctic - Darcy G. McNicholl; Colin P. Gallagher; Richard Gordon; Tyler Carmichael; Ryan McLeod; Joe Illasiak; Leona Kayotuk; Max Kotokak; Sarah Lord; Jasmine Brewster; Sarah Buckle; Cora-Lee Simpson; et al. (Environmental Biology of Fishes, 2025)
The cumulative effects of climate change are impacting Arctic species and facilitating increased interactions between Arctic and sub-Arctic species. Anadromous Arctic char Salvelinus alpinus and the northern Dolly Varden Salvelinus malma malma are endemic Arctic fishes vulnerable to the impacts of climate change, yet our understanding of the dietary niches they occupy is limited. The recent increased occurrence of sub-Arctic Pacific salmon ( Oncorhynchus spp.) in the western Canadian Arctic has raised concerns among Indigenous communities given the potential for competition with endemic fishes important for subsistence fisheries. Stable isotopes (δ 13 C and δ 15 N) were analyzed from Arctic char, Dolly Varden, and chum salmon Oncorhynchus keta , collected among four coastal Canadian Beaufort Sea locations. These fishes were captured during the summer of 2017 and 2019 during ongoing community-based fisheries monitoring programs in the Inuvialuit Settlement Region and Gwich’in Settlement Area. The trophic position of Arctic char and Dolly Varden indicates both species rely heavily on pelagic prey enriched in δ 15 N, consistent with a diet of marine forage fishes. Chum salmon occupied a trophic position > 3.0‰ below the char species, which reflects a diet comprised primarily of marine invertebrates. Isotopic niche analyses revealed chum salmon do not overlap in diet with the char species during the summer marine foraging season, and thus were unlikely to compete for prey as adults. This assessment of dietary overlap informs conservation and fisheries co-management objectives of endemic fishes as their as interactions with range-expanding species become more prevalent within a rapidly changing Arctic.